THE EFFECT OF CASH ACCOUNTING SYSTEM ON INTERNAL CONTROL OF ACCOUNTS IN PT. BANDUNG MP 2012-2014 - Titto Rohendra; Mohd Haizam Saudi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The risk of accumulation of accounts receivable can have a negative impact on the company's finances. For this reason, one of the management efforts in internal control of accounts receivable is the management of the cash accounting system. Problems that may be experienced in controlling accounts receivable can be constrained internally, namely the receivables are uncollectible. In this study, analyze the impact of their influence on the cash accounting system of internal control of accounts receivable, which are shown in the regression equation was y = 22,677 + 0,674x + e, and the result t statistical (5,717) greater than t critical (2,011) and Sig. 0,000 smaller than ? (0,05). With these results, it can be indicated that the cash accounting system with internal control over the receivables has a positive and significant effect.